Strong convergence of an iterative algorithm involving nonlinear mappings of nonexpansive and accretive type. (2nd September 2018) - Qin, Xiaolong; Cho, Sun Young; Wang, Lin
ABSTRACT: In this paper, a new iterative method for finding the projection onto the intersection of two closed convex sets in the framework of Banach spaces is presented. It is a viscosity approximation method which produces a strongly convergent sequence.